The story of Henrietta Lacks: an opportunity to make up for past mistakes - Bonsignore, Alessandro; Ventura, Francesco (Medicina Historica, 2022)
In the current time, when COVID-19 is disproportionately affecting Black people in several countries, the Henrietta Lacks’s centennial year remembers the responsibility to guide in a fairer era of research. The cells of Henrietta Lacks, taken without her consent, have been reproduced billions of times for medical purposes. The Henrietta Lacks’s anniversary urges to face with an issue still unsolved, since the consent to the collection of patients’ data, the methods of their archiving and their possible dissemination remains a complex question that is largely outstanding so far. In addition, the anniversary - in such a pandemic era - represents an opportunity to make up for past injustices and discrimination of the healthcare system.